Productivity enhancement of continuous miners packages of underground mines with energy conservation in industrial sectors - Mohd Ahtesham Hussain Siddiqui; Somnath Chattopadhyaya; Shubham Sharma; Changhe Li; Yanbin Zhang; Abhinav Kumar; Dražan Kozak; Mohamed Abbas; Jasmina Lozanovic (Energy Exploration & Exploitation)
Energy auditing is crucial for both emerging and developed nations, focusing on aspects such as energy efficiency, quality and intensity. This becomes especially significant in the industrial sector, where major operating costs involve materials, machinery, personnel and energy. A key objective is identifying energy consumption in the Continuous Miner Machine, boasting a 1050 KW connected load, to explore opportunities for energy savings and improved quality. The execution of an energy audit promises increased efficiency, enhanced power quality, reduced costs and prevention of energy wastage. This research study has meticulously examined the electrical equipment supplying power to Continuous Miner Machines, proposing modifications to boost production through energy-efficient methods. Comprehensive assessments of primary substations, including Incomers, Transformers, Feeders, etc., involve tests for voltage, current, power factor, harmonics and AC waveform. Thermal imaging is employed to analyze the operational temperature of the electrical equipment. The graphical representations of test outcomes have highlighted a significant recommendation: installing an Automatic Power Factor Controller on the inductive load side of transformers could lead to a notable 3.85% reduction in energy costs.